AUTOMATION OF THE ASSETS SECTOR OF THE AMAZON FOUNDATION FOR SUPPORTING STUDIES AND RESEARCH PARÁ: WAYS TO OPTIMIZE THE INVENTORY SURVEY - Nobre, Fábia Jaqueline Miranda; Monteiro, Alessandra Mendes (Seven Editora, 2026)
This study focuses on the asset management of permanent assets at the Amazon Foundation for Support of Studies and Research of Pará (FAPESPA). The objective is to present a discussion on the feasibility of adopting Radio Frequency Identification (RFID) technology to automate the asset management of FAPESPA's inventories within the Sispatweb system. It will address the verification of the components of the asset management sector for the operational management of the system; the identification of the operational structure of SISPAT WEB for the integration of the technology and optimization of the time required for conducting the internal institutional inventory. Qualitative research was the method used, of an exploratory nature, employing bibliographic and documentary research. The data collection period was 2014-2024. The results showed that technological strategies can prevent potential human errors; optimizing the inventory process leads to improved occupational safety for employees, preventing occupational diseases such as Repetitive Strain Injury (RSI) and Work-Related Musculoskeletal Disorders (WRMD), aiming to achieve the objectives of axis III of the A3P agenda ODS12.DOI: https://doi.org/10.56238/sevened2026.008-107